Reactions of 4-(p-Methylbenzoyl)-5- (p-methylphenyl)furan-2,3-dione with Various Anilides - OZER ILHAN, ILHAN; ALTUNTAS, EMINE; YILDIRIM, ISMAIL (Asian Journal of Chemistry, 2010)
4-(p-Methylbenzoyl)-5-(p-methylphenyl)furan-2,3-dione (1) reacts with acetanilides (3a-f) under different conditions and gives open-chain dibenzoylacetic acid derivatives 4a,b, 5c-f. It has been demonstrated that with the variation in reaction conditions, the reaction changes leading to different products. All the newly synthesized compounds were characterized by elemental analysis, IR, 1H and 13C NMR spectral data. All were compared with their previous analogues.